Investigation of the solid-state [2+2] photodimerization of trans-4-(trifluoromethyl) cinnamic acid via thermogravimetry (Bulletin of the Institute of Chemistry and Chemical Technology, 2024)
Compared to spectroscopic methods, thermal methods are rarely used investigate the kinetics of the reactions in the solid state because temperature influences reaction rates and can trigger reverse reactions. However, if the photoreaction is thermally irreversible, it is possible to determine reaction kinetics via thermal methods effectively. In this work, we investigated the solid-state [2+2] photodimerization of trans-4-(trifluoromethyl) cinnamic acid (a derivative of trans-cinnamic acid) using thermogravimetric analysis. The photodimerization product 4,4'-ditrifluoromethyl truxinic acid, containing a cyclobutane ring, decomposes at a higher temperature than the reactant trans-4-(trifluoromethyl) cinnamic acid, enabling the determination of conversion progress by thermogravimetric analysis. The photodimerization kinetics in the solid state was found to follow the JMAK model and the corresponding kinetic parameters were determined.Транс-4-(трифлуорометил) фенилпропионы хүчлийн хатуу төлөвийн [2+2] фотодимержих урвалын термогравиметрийн судалгааГэрлийн нөлөөнд хатуу төлөвт явагддаг урвалын кинетикийн судалгаанд дулааны аргуудаас илүүтэйгээр спектроскопын аргуудыг ашигладаг. Энэ нь температур урвалын хурдад хүчтэй нөлөөлөхөөс гадна зарим тохиолдолд эргэх урвалыг өдөөдөгтэй холбоотой юм. Гэвч дулааны нөлөөнд эргэх урвалд ордоггүй фотохимийн урвалын кинетикийг дулааны аргуудаар судлах боломжтой. Тиймээс бид энэ ажлаар транс-фенилпропионы хүчлийн уламжлал болох транс-4- трифлуорометил фенилпропионы хүчлийн хатуу төлөвийн [2+2] фотодимержих урвалыг термогравиметрийн аргаар судлав. Транс-4-трифлуорометил фенилпропионий хүчлийн фотодимержих урвалын бүтээгдэхүүн циклобутан цагираг бүхий нэгдэл 4,4’-дитрифлуорометил труксиник хүчил нь эх бодисоосоо өндөр температурт задардаг учир фотодимержих урвалын гарцыг термогравиметрийн аргаар тодорхойлох боломжтой болсон. Улмаар транс-4-трифлуорометил фенилпропионий хүчлийн фотодимержих урвал нь JMAK кинетик зүй тогтлын дагуу явагддаг болохыг тогтоож холбогдох кинетик параметрүүдийг тодорхойлов.Түлхүүр үг: термогравиметр, хатуу төлөв, фотохими, фотодимеризаци